Hierarchically Structured Ultraporous Iridium‐Based Materials: A Novel Catalyst Architecture for Proton Exchange Membrane Water Electrolyzers. Issue 4 (3rd December 2018) - Faustini, Marco; Giraud, Marion; Jones, Deborah; Rozière, Jacques; Dupont, Marc; Porter, Thomas R.; Nowak, Sophie; Bahri, Mounib; Ersen, Ovidiu; Sanchez, Clément; Boissière, Cédric; Tard, Cédric; et al.
Abstract: Iridium oxide is the gold‐standard catalyst for the oxygen evolution reaction (OER) in acidic media due to its unmatched activity and stability. Here, a new catalyst architecture comprising a nanoneedle network of iridium‐containing oxides assembled into macroporous micrometric particles with ≈75% of porosity is reported. The rationally designed porous hierarchical structure optimizes the accessibility of reactants and products to the surface of the nanoparticles and maximizes catalyst activity. The materials are easily prepared from aqueous solutions by an industrially viable spray‐drying route through an evaporation self‐assembly mechanism. The versatility of the process enables the preparation of mixed oxides with low iridium content, particles with tunable crystallinity, and various iridium surface species with high electrochemical activity. Highly porous Ir0.7 Ru0.3 O2 outperforms commercial iridium oxide. These materials also represent an ideal platform to assess the reactivity of the iridium and oxygen species involved in the oxygen evolution reaction. Furthermore, it is demonstrated that these highly porous particles are optimal building blocks to be integrated into catalyst layers, without the drawbacks associated with the use of discrete nanoparticles. Fresh‐ and end‐of‐test membrane–electrode assemblies' characterization shows that their particular architecture is preserved upon catalyst layer preparation and after operation in a proton‐exchange membrane electrolysis cell. Abstract : Ultraporous nanocrystalline IrO x microspheres are optimal architectures to build highly porous catalyst layers. Easily prepared by a spray‐drying process, they consist of a nanoneedle network of iridium‐containing oxides assembled into macroporous micrometric particles with ≈75% of porosity. While being very active toward the oxygen evolution reaction, their morphology is maintained when assembled and tested in a proton exchange membrane electrolysis cell.